THE COMPARISON OF THE TAX RATES BETWEEN THE REPUBLIC OF KOSOVO WITH COUNTRIES IN REGION AND THE EUROPEAN UNION COUNTRIES - Vehbi Imeri (European Scientific Journal, ESJ, 2013)
This paper contains the comparative analysis of some taxes and social security contributions which are of most importance having an impact on the decisions of the investors for investments and opening new jobs and sustainable economical development.This comparison of the tax rates and social insurances is made between the Republic of Kosovo and countries in the region and the European Union countries (Albania, Macedonia, Montenegro, Croatia, Bosnia and Herzegovina and Serbia).The targets of the comparison are tax rates and social securities as follows:1. The tax on incomea) Corporate taxb) Taxed on individual – personal incomes2. Social securitya) Social security paid by employeesb) Social security paid by employersc) Health insurance paid by employeesd) Health insurance paid by employerse) Health insurance at workf) Social Security from unemployment paid by the employeesg) Social Security from unemployment paid by the employers3. VAT (Value Added Tax)